Analisis dan Desain Sistem Informasi Penelitian dan Pengabdian Masyarakat (Simpenmas) Politeknik Negeri Lhokseumawe - Hidayat, Hari Toha; Amin, Haris Al; Mursyidah, Mursyidah; Atthariq, Atthariq (Elinvo (Electronics, Informatics, and Vocational Education), 2019)
Information systems of research and community service need to be developed to improve the management of research outputs and community service outcomes by lecturers while making it easier to evaluate tertiary accreditation. This system was developed using the waterfall model. This article aims to describe the stages of system development consisting of: (1) investigating user needs; (2) data and needs analysis in the process of making a system; (3) design; and (4) implementation. The result is the need for a system that specifically can provide facilities for uploading research outputs and community service such as journal publications, textbooks / texts, and scientific forum speakers. In addition to other mandatory menus, menus that are also being developed are the daily notes menu and the progress report menu. The design stages produce the design of the menu flow. The implementation stages of the research and community service information system use PHP language using the Laravel framework. Future studies need to test the use of systems that can use Apache jmeter and Selenium.